Artificial Intelligence in the English Classroom: Middle School Teachers' and Students' Perceptions - Dinn Islam, Ikhsan; Syafrizal, Syafrizal; Juniardi, Yudi (STAIRS: English Language Education Journal, 2024)
As artificial intelligence (AI) continues to revolutionize various sectors, its application in education, particularly language learning, is gaining attention. AI tools offer new possibilities for personalized instruction, adaptive feedback, and time-efficient learning experiences, making them increasingly relevant in modern classrooms. However, while global research on AI-assisted language learning is expanding, there is still limited understanding of how AI integration is perceived at the classroom level, particularly in under-researched contexts such as rural or faith-based schools in Indonesia. This study aims to address this gap by exploring the perceptions of students and teachers at SMP 1 Nurul Basmalah regarding the use of AI in English language instruction. Using a qualitative approach through focus groups and interviews, the findings suggest that AI can save students’ time and offer personalized learning experiences through interactive engagement. However, concerns remain about teacher readiness and the reliance on electronic devices, emphasizing the need for professional development. Furthermore, this study highlights the importance of identifying both the strengths and limitations of AI in education, promoting ethical usage, and developing practical strategies to enhance learning outcomes and foster student creativity.